Some Difficulties and Suggestions for Sustainable Marine Eco-tourism in Vietnam and Japan: Case Studies of Vân Đồn District, Quảng Ninh Province and Akkeshi Town, Hokkaido - Haruo, Noma; Thanh, Trần Đức; Hoa, Trần Thị Mai (VNU Journal of Science: Earth and Environmental Sciences, 2013)
Abstract. The paper deals with the difficulties in developing sustainable marine eco-tourism based on analysis of current situation in two case studies inJapan andVietnam.AkkeshiTown is located in the northeastern part ofHokkaido, where the natural resources are abundant, such as the Ramsar inscribed wetland, the existence of big mammals such as seals. However, the town is facing the decrease in the number of visitors after a high expectation in the 1990s due to an out-of the way place. Vân Đồn District, on the other hand, is a new and prospective project in the government’s policy to stimulate the economy of the coastal zone of Quảng Ninh. It owns a national park that offers a lot of natural resources but a proper way is yet to be found to make it conform with the exploitation of tourism industry. Besides the diversity in geographical features, it is also the habitat of some kinds of tortoises and other special animals. Nevertheless, both cases have similar paradoxes in tourism development, first from the objective contexts (e.g. the competition with their neighboring areas that have quite similar natural resources) and secondly, from the subjective paradigms (e.g. the high seasonableness and dependency on natural conditions). How to minimize the difficulties to support the development of ecotourism is the question that needs correct answers. Based on the authors’ experience in tourism industry, some solutions are suggested, including co-operation within local tourism, the proactive leadership of local government, the business model for sustainable management, as well as considering the interaction relationship between mass tourism and ecotourism as a solution for current development. Keywords: Ecotourism, sustainable tourism, tourism management, Vietnam, Japan.